MANAGEMENT TRANSFORMATION OF WARGA VOCATIONAL SCHOOL TOWARD A CENTER OF EXCELLENCE VOCATIONAL SCHOOL: A CASE STUDY OF THE PROCESS, CHANGES, AND IMPACTS ON THE TEACHING FACTORY - Alvian Arsennio Putra; Valiant Lukad Perdana Sutrisno (Jurnal Dinamika Vokasional Teknik Mesin, 2026)
This study aims to reveal the transformation process of the management of SMK Warga Surakarta in achieving the status of SMK Center of Excellence (SMK PK) and to find out the changes and impact of the SMK PK program on the implementation of the Teaching Factory (TEFA). The research uses a qualitative descriptive approach with a case study method. Data collection was carried out through interviews and documentation involving school principals, heads of the TEFA program, and teachers. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing with triangulation techniques to ensure the validity of the data. The results of the study show that the transformation towards SMK PK is carried out in stages through the process of program submission, selection, verification, and program implementation. In this process, the school implements management strategies in the form of synchronization with the industrial world, strengthening TEFA learning, and optimizing human resources and school facilities. The implementation of the SMK PK program provides changes to the implementation of TEFA, characterized by a more structured learning system, more organized administrative and managerial systems, improvements in facilities and infrastructure, and more student-centered learning methods. In addition, the PK Vocational School program also has an impact on improving student competence, teacher quality, learning quality, and increasing cooperation and industry trust in schools. This research contributes to enriching the study of the transformation of school management towards a Center of Excellence Vocational School and shows that strengthening TEFA through the PK Vocational School program can be an effective strategy in improving the quality of vocational education in line with industry needs.